STATUS KEBERLANJUTAN PENGELOLAAN PERKEBUNAN INTI RAKYAT KELAPA SAWIT BERKELANJUTAN DI TRUMON, KABUPATEN ACEH SELATAN - Nurul Lainan Najmi; Al Jaktsa Al Jaktsa; Suharno Suharno; Anna Fariyanti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
This study aims to evaluate the sustainable status of oil palm plantation management and determine the most dominant attributes to sustainability in Trumon, South Aceh Regency. Data analysis using Multi Dimensional Scalling method and sensitivity analysis. The results of the analysis of the sustainability status of oil palm plantations, index values of each dimension with dimensions of 64,04, technology dimensions 53,26, economic dimensions 48,83, demonstration dimensions 45,54, and the lowest index values according to the social dimension 35,92. There are nine main attributes or key factors related to the sustainability of the management of oil palm plasma nucleus plantations, namely: 1) residents working in the plantation sector, 2) time and method of providing fertilizer to harvest, 3) FFB prices at farm level, 4) accessibility of farmer groups to banks, 5) land management administration, 6) Village communication accessibility, 7) farmer groups, 8) use of land and air conservation technology, 9) Management of crop disturbing crops (OPT). Index of multi-dimensional sustainability of oil palm plantation management nucleus-plasma pattern is 49,10 means that the sustainability status is still lacking. This has an impact on reducing involvement in agribusiness activities, lack of farmers' participation in farmer groups and KUD, because the role of this institution to access capital to banks does not support formal education, so that communication between farmers and institutions is inadequate.